TARI DOGER KONTRAK SEBAGAI SUMBER GARAP PENYAJIAN TARI - Derra Dwi Dessyani dan Lia Amelia (Jurnal Seni Makalangan, 2018)
ABSTRAK Tari Doger Kontrak adalah penyajian tari ronggeng, dengan diilhami oleh bentuk kesenian Doger dari Subang yang telah dijadikan garapan baru. Istilah Doger menunjuk pada penari wanita yang disebut ronggeng dalam kesenian Ketuk Tilu, sementara Kontrak merupakan nama sebuah tempat perkebunan kina di Jawa Barat. Biasanya pegawai perkebunan itu pun disebut sebagai pegawai kontrak.Penyajian Tari Doger Kontrak, disusun dengan menggunakan pendekatan teori “gubahan tari” A.A.M Djelantik. Penyajiannya dalam bentuk koreografi kelompok dengan tujuh orang penari wanita yang semuanya berperan sebagai ronggeng.Kata Kunci: Tari Doger Kontrak, Gubahan Tari.   ABSTRACT Doger Kontrak Dance is the presentation of ronggeng dance, inspired by Doger art from Subang, which was produced by Dance Department of ASTI Bandung as a new dance work. The term of Doger refers to female dancers called ronggeng in Ketuk Tilu art, while the word Kontrak (Contract) is the name of a plantation site that the West Javanese community in the past called it a tea contract or quinine contract, even the plantation employees are usually called as contract employees.The presentation of Doger Contract Dance is realized by using "dance composition" by A.A.M Djelantik. As a result, the realization of Doger Contract dance as a new packaging dance work without losing its essence, and presented as group choreography with seven female dancers performing as ronggeng.Keywords: Doger Kontrak Dance, Dance Composition.